Pengaruh Pemasaran Digital Melalui Fitur Tiktok Live Akun @Kattoen Terhadap Keputusan Pembelian - Arya Nanda Aji Say; Sri Murdilah Fournawati; Fen Irianti (Social Science Academic, 2023)
This research is entitled "The Influence of Digital Marketing Through the TikTok Live Account @kattoen Feature on Purchasing Decisions". This research aims to determine the influence of digital marketing through the TikTok live feature on consumer purchasing decisions. This research uses the AIDA theory which is an abbreviation of Attention, Interest, Desire, Action. In marketing it is necessary to formulate the goals to be achieved from the communication process carried out, and AIDA is a concept that plays an important role in marketing activities. The paradigm used in this research is the positivism paradigm with quantitative research methods. The researcher used data collection techniques carried out through questionnaires and data analysis techniques using a Likert scale. The population used in this research were followers of the @kattoen account, numbering 283 thousand with The sample obtained was 100 respondents. The sampling technique was Nonprobability Sampling. The results of this research show that there is a positive and significant influence of the live streaming variable on purchasing decisions as shown by the results of the coefficient of determination analysis test which shows that the R Square value is 0.781, which means the live streaming variable has a positive influence on purchasing decisions of 78.1%.